Eco‐morphological attributes and feeding habits in coexisting characins. Issue 1 (12th October 2016) - Portella, T.; Lobón‐Cerviá, J.; Manna, L. R.; Bergallo, H. G.; Mazzoni, R.
Abstract : The head morphology and feeding habits of pairs of characin species (family Characidae) that coexist in four different coastal rainforest streams were analysed. Coexisting species differed in size, but were very similar in eco‐morphological attributes. Gut analyses revealed differences in feeding preferences for each coexisting species, indicating resource partitioning. A pattern of organization in species pairs that was repeated in the four studied streams was noticed. The pattern consisted of one slightly larger species with a feeding preference for items of allochthonous origin and another smaller species with a preference for autochthonous items. The hypothesis that small morphological differences enable the current coexistence of those species pairs was proposed. Furthermore, the results show ecological equivalence among different species in the studied streams.